MONITORING OF DRINKING WATER QUALITY IN THE REFERENCE POINTS OF THE DISTRIBUTION NETWORK OF RWC "RADONIQ" GJAKOVA - Daija, Luan; Kepuska, Xhelal; Shehu, Leonard (European Scientific Journal, ESJ, 2014)
Control and monitoring of water quality indicators in RWC "Radoniqi" Gjakova is carried out in compliance with the requirements specified in the Administrative Instruction nr.16/2012 for water quality for human consumption. Regular internal monitoring of water quality for human consumption is carried out to check that the water is potable and that it meets the requirements of this administrative directive, and in particular, set parametric values. Monitoring includes inspection, measurements, samplings or analysis either periodically or continuously. Monitoring indicators of drinking water quality in reference points of the distribution network of RWC "Radoniqi" Gjakova is carried by two laboratories for monitoring of physicalchemical and bacteriological parameters. In the laboratories for analysis of water quality indicators in the reference points of the distribution network of RWC "Radoniqi" Gjakova, is carried out water quality monitoring for physical-chemical and bacteriological indicators according to a particular timeline in the following locations: the Reservoir in Treatment Plant Radoniqi, Reservoir Qerim, City Ambulance, Hospital, the main reservoir in Rahovac, Health Center Rahovac, Petrol station in Krusha e vogël. Parameters to be analyzed: Physical-chemical indicators: determination of free chlorine, water temperature, m - alkaline, air temperature, pH value, dry residue, turbidity, total hardness, color, taste, electrical conductivity, iron, manganese, KMnO4 (permanganate) value, NH4 + ammonium, dissolved oxygen, nitrites, chlorides, etc. Bacteriological indicators: these are analyzed bacteriological parameters such as: total number of coliform bacteria in 100 ml of water, fecal origin coliform bacteria per 100 ml, total number of viable bacteria in 1 ml. From the results obtained in the laboratory can be concluded that the treated water of RWC "Radoniqi" is of good quality and that it meets standards according to WHO, EU and Administrative Instruction nr.16/2012 for drinking water quality for human consumption.